Transport's historical, contemporary and future role in shaping urban development: Re-evaluating transit oriented development - Knowles, Richard D.; Ferbrache, Fiona; Nikitas, Alexandros (Cities, 2020)
This paper reviews transport's historical, contemporary and future role in shaping urban development since industrialisation. Previous definitions of Transit Oriented Development (TOD) starting in the late 20th century are challenged. Three distinct eras of TOD are identified: from the mid-19th century to early 20th century; Planned TOD in the mid-20th century; and TOD for urban regeneration and/or urban expansion since the late 20th century, now featuring rail and bus rapid transit, cycling and walking, shared use mobility, and automated transport. Future links with disruptive transport technologies are highlighted as themes that must be examined for assisting TOD's further development. The authors make the case, using empirical evidence from selected TOD applications from around the world, that high frequency transit service is essential for successful contemporary and future planned TODs. TOD is then redefined for the 21st century and best practice policy recommendations are made.